A Software Test Data Generation Tool for Unit Testing Of C++ Programs Using Control Flow Graph (International Journal of Engineering and Computer Science, 2013)
Software quality and assurance in a software companyis the only way to gain the customer confidence by removing all possible errors. It can be done by automatic test case generation. Taking popularly C++ programs as tests object, this paper explores how to create Control flow graphs of a C++ program and generate automatic Test Cases. It explores the feasibility and non- feasibility of path basis upon no. of iteration. First C++ is code converted to instrumented code. Then test cases are generated by using Symbolic Testing and random Testing. System is developed by using C#.net in Visual Studio 2008. In addition some future research directions are also explored